1997
DOI: 10.1136/jcp.50.6.472
|View full text |Cite
|
Sign up to set email alerts
|

Enterocytozoon bieneusi in AIDS: symptomatic relief and parasite changes after furazolidone.

Abstract: Aims-To investigate changes in morphology ofthe developmental stages ofEnterocytozoon bieneusi and symptomatic relief observed in AIDS patients after treatment with furazolidone. Methods-Six AIDS patients with symptomatic E bieneusi infection of the small intestine were treated with a course of furazolidone. All patients had a weekly monitoring of parasite shedding in stool by light microscopy during and after treatment. At the end of the treatment, duodenal biopsy specimens obtained from three patients were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
13
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 16 publications
4
13
0
Order By: Relevance
“…30 Clinical signs of diarrhea and wasting associated with E. bieneusi are reported to improve with albendazole, thalidomide, fumagillin, or furazolidone therapy, but elimination of infection has not been confirmed with these compounds. 45,47,90,125 In a more recent study, clindamycin was suggested to be efficacious against E. bieneusi infection. 72 Encephalitozoon intestinalis (originally named Septata intestinalis) was differentiated from Enterocytozoon bieneusi in 1993 as yet another agent of chronic diarrhea and weight loss in AIDS patients.…”
Section: Microsporidiosis As An Emerging Human Diseasementioning
confidence: 99%
“…30 Clinical signs of diarrhea and wasting associated with E. bieneusi are reported to improve with albendazole, thalidomide, fumagillin, or furazolidone therapy, but elimination of infection has not been confirmed with these compounds. 45,47,90,125 In a more recent study, clindamycin was suggested to be efficacious against E. bieneusi infection. 72 Encephalitozoon intestinalis (originally named Septata intestinalis) was differentiated from Enterocytozoon bieneusi in 1993 as yet another agent of chronic diarrhea and weight loss in AIDS patients.…”
Section: Microsporidiosis As An Emerging Human Diseasementioning
confidence: 99%
“…The drug fumagillin has also demonstrated good anti-Enterocytozoon bieneusi activity (40,57,195), although various adverse side effects have been documented (56,141,194,195). The drug furazolidone has also demonstrated a degree of anti-Enterocytozoon activity (74). As with most opportunistic infections, HAART plays a key role in eradicating microsporidia in HIV-infected patients (105), and effective HAART is likely to reduce the incidence of microsporidial infections in the future.…”
Section: Microsporidiamentioning
confidence: 99%
“…However, significant thrombocytopenia and neutropenia occurred in three out of the six patients in the treatment arm. Furazolidone, on the other hand, was found to provide symptomatic relief and decreased parasite shedding but not eradication in the stools of six patients with AIDS and E. bieneusi [129]. A further study by the same group using the combination of this drug with albendazole again failed to demonstrate eradication of the parasite [130].…”
Section: Microsporidiosismentioning
confidence: 92%